1988
DOI: 10.21273/jashs.113.1.70
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Temperature-controlled Leaf Unfolding Rates in ‘Nellie White’ Easter Lily

Abstract: The rate of leaf unfolding was determined for Easter lily (Lilium longiflorum Thunb.) ‘Nellie White’ grown at day and night temperatures ranging from 14° to 30°C. In this temperature range, rate of leaf unfolding was a linear function of average daily temperature; i.e., the effect on rate of leaf unfolding for day temperature was the same as for night temperature. The function determined was: leaves unfolded per day = −0.1052 + (0.0940 × average daily temperature). Isopleth plots were developed to describe day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Petunia species produce a single leaf per node, therefore node appearance rate and leaf unfolding rate can be used interchangeably as quantifications of development rate. Leaf unfolding rate is temperature responsive, increasing with higher temperatures up to a genotype-specific maximum temperature (Tollenaar et al 1979;Karlsson et al 1988Karlsson et al , 1989Truong and Duthion 1993) and declining if temperature exceeds the maximum. However, different species and even different cultivars of a species exhibit different rates at the same temperature (Tollenaar et al 1984;Padilla and Otegui 2005), suggesting that it should be possible to breed for individuals with faster development rate.…”
mentioning
confidence: 99%
“…Petunia species produce a single leaf per node, therefore node appearance rate and leaf unfolding rate can be used interchangeably as quantifications of development rate. Leaf unfolding rate is temperature responsive, increasing with higher temperatures up to a genotype-specific maximum temperature (Tollenaar et al 1979;Karlsson et al 1988Karlsson et al , 1989Truong and Duthion 1993) and declining if temperature exceeds the maximum. However, different species and even different cultivars of a species exhibit different rates at the same temperature (Tollenaar et al 1984;Padilla and Otegui 2005), suggesting that it should be possible to breed for individuals with faster development rate.…”
mentioning
confidence: 99%
“…This rate of increase in leaf unfolding per I o increase in ADT is comparable to pea with 0.020 leaves/°C per day (Balvoll and Bremer, 1965) and to sunflower with 0.022 leaves/°C per day (Rawson and Hindmarsh, 1982). However, the rate of leaf unfolding was five times slower than Easter lily at 0.094 leaves/ °C per day (Karlsson et al, 1988) and four times slower than maize at 0.067 leaves/°C per day (Tollenaar et al, 1979).…”
Section: Resultsmentioning
confidence: 64%
“…Rate of leaf appearance in several species has been found to increase linearly to a maximum rate as temperature increases (Friend et al, 1962;Balvoll and Bremer, 1965;Tollenaar et al, 1979;Rawson and Hindmarsh, 1982;Karlsson et al, 1988). Cockshull et al (1981) reported that leaf appearance in chrysanthemum was also an average daily temperature (ADT) response.…”
Section: Resultsmentioning
confidence: 99%